The health care needs of multidimensional frail elderly patients with multimorbidity in primary health-care settings: a qualitative study - Zhao, Linlin; Chang, Bingjie; Hu, Qinghua; Chen, Xiaolei; Du, Juan; Shao, Shuang (BMC family practice, 2025)
Our study aimed to explore the health care needs of older adults with multimorbidity assessed as multidimensional frailty from their perspective in Beijing, China, in primary health-care settings. This study was conducted using a qualitative approach involving semi-structured interviews of 21 participants at the Outpatient clinic, in four primary health care institutions (PHCIs), Beijing, China. The subjects were drawn from a cross-sectional survey that assessed multidimensional frailty in older adults with multimorbidity. The participants meeting the criteria were selected through purposive sampling until subject saturation. The interviews were transcribed and organized verbatim and then subjected to thematic analysis using inductive approach. A total of four themes on the needs of the multidimensional frail elderly patients with multimorbidity were identified, including improving physical functioning, adjusting psychological status, obtaining social support, and choosing health care modalities. Improving physical functioning was their co-occurring need, regardless of the score on the physical frailty dimension. In contrast, it is when increased psychological and social frailty has an impact on physical functioning that might drive patients to develop psychological and social demands. This exploratory study is helpful to understand the healthcare needs of the multidimensionally frail elderly patients with multimorbidity from the perspectives of individuals, families, and society, in turn formulate healthcare promotion strategies. Appropriate policies and measures should be taken, such as integrating multidimensional frailty assessments into current multimorbidity management protocols, developing personalized interventions centered on patient needs, conducting family function assessments and caregiver training programs, and enhancing the integration of social resources.